Accelerated photocarcinogenesis and multifocal squamous cell carcinomas associated with voriconazole and human papillomavirus in HIV – case report. (January 2023) - Haddad, Salma; Younis, Ibby; Bakkour, Waseem; Waters, Laura Jane; Perrett, Conal; Ratynska, Marzena; Bunker, Christopher B
Voriconazole is an antifungal with known side effects of phototoxicity and photocarcinogenesis. We present a case of HPV-related multifocal squamous cell carcinoma in a 68-year-old man with HIV, due to accelerated photocarcinogenesis associated with long-term use of voriconazole. Histology confirmed SCC with HPV-related features and he was found to have metastases. Multifocal SCC is unusual in association with voriconazole and HIV infection and only one other case has been reported. It is important for clinicians to be aware of the photocarcinogenic effects of voriconazole, especially in patients with HIV.